Legionnaires Disease - R., Sandeep K.; S., Sandhya Rani B. (Journal of Health and Allied Sciences NU, 2018)
Legionnaires' disease is a form of atypical pneumonia caused by any type of Legionella bacteria. The bacterium is found naturally in fresh water.[4] It can contaminate hot water tanks, hot tubs, and cooling towers of large air conditioners.[4] It is usually spread by breathing in mist that contains the bacteria.[4] It can also occur when contaminated water is aspirated.[4] It typically does not spread directly between people and most people who are exposed do not become infected.[4] Risk factors for infection include older age, history of smoking, chronic lung disease, and poor immune function.[5] There is still a low level of clinical awareness regarding Legionnaires' disease 25 years after it was first detected.
Keywords: Legionella bacteria; Relative bradycardia; Pontiac fever; pneumonia